Evaluation of The Drug Storage System at The Welahan II Health Center Based on The Minister of Health Regulation No. 74 of 2016 - Dea Safira; Zaenal Fanani; Muhammad Nurul Fadel (Advances in Healthcare Research, 2026)
Purpose: This study aimed to evaluate the compliance of the drug storage system at Welahan II Community Health Center with the standards set in the Minister of Health Regulation No. 74 of 2016. It was hypothesized that the storage system would exhibit high compliance, although several aspects of the physical infrastructure might still require improvement. Research Method: This study used a quantitative descriptive-evaluative design with a cross-sectional approach. Data were collected in February 2026 through direct observation using checklists, structured interviews, and documentation in the pharmaceutical warehouse of Welahan II Community Health Center. The evaluation covered spatial arrangement, stock preparation, separation of special drugs, observation of drug quality, and recording on stock cards. Data were analyzed descriptively by calculating the percentage of compliance with regulatory indicators. Results and Discussion: The overall average compliance was 93%, categorized as very good. Perfect compliance (100%) was achieved in special drug separation, physical quality observation, and stock card recording. Stock preparation reached 90%, while spatial arrangement had the lowest score (75%) due to limited warehouse space and non-standard room layout. Implications: The findings indicate that strong administrative and technical discipline can compensate for infrastructure limitations in maintaining drug quality and patient safety. Further studies should assess the effect of storage compliance on service efficiency and medication error prevention.